Land Dispute Settlements Insocial Philosophy Perspectives(A Case Study in PTPN VII of Bergen Unit Business in South Lampung Regency) - Herlina Ratna S.N. (UBL, 2013)
Land dispute is a complicated problem, especially when this problem includes some parties or masspublic. The rise of land dispute is caused by inequality of land possessing and control amongstgovernment, state plantation, private, and tenant farmers. Land dispute in Sidodadi Asri versus PTPerkebunan Nusantara VII is a conflict of land control based on Right to Cultivate (or HGU) and erfpachtright which was a conversion from colonial law upon land control of colonialist heritage that causedeffects such as eviction and expulsion with force to tenant farmers. The objective of this research is tostudy event chronologies causing the land dispute, to elaborate causing factors, to identify efforts thathave been done, and to find out solutions upon land dispute based on social approach. This research isstudied through social philosophy approach and descriptive analysis.Land dispute in Sidodadi Asri village of South Lampung regency has been occurring since 1999.Many efforts of settlements had been conducted either by means of traditional mediation, formal method(court), or land mediation which was formed in environment of National Land Agency (or BPN). Courtsettlement and mediation did not always give solutions to satisfy and give sense of justice for public.Main findings in this research are that [1] land disputes cause miseries to tenant farmers; [2] land disputecausing factors are historical backgrounds; [3] based on philosophical perspective, land disputes are statenegligence in making provisions that regulate basic natural rights of people upon land, and based ontheology philosophy and limited state power; a state is built by people and to welfare people and thisbecome philosophical foundation from egocentric ethic; [4] the land dispute involving public requiressettlements based on social, culture and theological aspects because land dispute settlement process basedon normative law always produces weak position for people; [5] reformation of right upon land rightcannot be limited by proof of possession, land use, or land control only, but it should embark fromdemocratic government policies oriented to tenant farmer welfare. Therefore, the Right to Cultivategranted by the state should not be absolute, but considering public and social factors.The author recommends philosophically and socially compromised efforts for land dispute settlementswith public by involving roles of limited state power and by not prioritizing law channel factors that causepeople miseries, and the efforts need to honor local wisdom values. Government should be wiser ingiving land right and more concern about local people’s interests who physically control the land, and togive proper compensation. Government should be able to improve social order with more justice relatedto land controlling, possessing, and using.